2021
DOI: 10.3390/ijms22137231
|View full text |Cite
|
Sign up to set email alerts
|

Metformin as a Treatment Strategy for Sjögren’s Syndrome

Abstract: Sjögren’s syndrome (SS), a chronic inflammatory disease involving the salivary and lacrimal glands, presents symptoms of sicca as well as systemic manifestations such as fatigue and musculoskeletal pain. Only a few treatments have been successful in management of SS; thus treatment of the disease is challenging. Metformin is the first-line agent for type 2 diabetes and has anti-inflammatory potential. Its immunomodulatory capacity is exerted via activation of 5’ adenosine monophosphate-activated protein kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…The result can be explained by metformin is regarded as the first-line therapy of type 2 DM and reduce the risk of developing SS in patients with DM through anti-inflammatory effect, furthermore, it has been considered as the treatment strategy for SS in the manner of enhancing the immunomodulatory response. 37 38 Another finding is low percentage of patients with SS had tumours and metastatic solid tumour and lower risk between herpes zoster exposure and SS in tumours patients. There is inconsistent information about overall risk of cancer, and little information about the solid cancer in SS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result can be explained by metformin is regarded as the first-line therapy of type 2 DM and reduce the risk of developing SS in patients with DM through anti-inflammatory effect, furthermore, it has been considered as the treatment strategy for SS in the manner of enhancing the immunomodulatory response. 37 38 Another finding is low percentage of patients with SS had tumours and metastatic solid tumour and lower risk between herpes zoster exposure and SS in tumours patients. There is inconsistent information about overall risk of cancer, and little information about the solid cancer in SS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Low percentage of patients with SS had dDM and lower risk between herpes zoster exposure and SS in DM patients. The result can be explained by metformin is regarded as the first-line therapy of type 2 DM and reduce the risk of developing SS in patients with DM through anti-inflammatory effect, furthermore, it has been considered as the treatment strategy for SS in the manner of enhancing the immunomodulatory response 37 38. Another finding is low percentage of patients with SS had tumours and metastatic solid tumour and lower risk between herpes zoster exposure and SS in tumours patients.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the etiology and pathogenesis are not fully known, studies have shown that Sjӧgren’s syndrome might be the result of various factors that include genetic predisposition, environmental factors, hormones, and immune dysregulation [ 3 ]. Sjӧgren’s syndrome patients have also been diagnosed in conjunction with other autoimmune diseases, such as rheumatoid arthritis, systemic lupus erythematosus (SLE), and systemic scleroderma [ [4] , [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the pathogenesis of pSS is not entirely comprehended, it has been shown that it can be a result of both innate and adaptive immune response; an increase in CD4 T cells induces inflammatory cytokines, which is directly related to the augmented secretion of B cells, a key feature of primary Sjӧgren’s syndrome, resulting in high secretion of autoantibodies, that precedes most autoimmune diseases [ 4 , 8 ]. More than 60% of patients suffering from pSS show irregular levels mostly of autoantibodies such as anti- SS-A/Ro or anti SS-B/La, muscarinic receptor, anti-fodrin receptor antibodies, and rheumatoid factor, causing aggravating symptoms and life-threatening comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin has shown its potency in treatment of dry eye disease caused by Sjögren's syndrome due to its ability to alleviate inflammation of lacrimal glands [8]. This effect was observed due to inhibition of NF-κB activation and AMPK activation in lacrimal glands.…”
Section: Introductionmentioning
confidence: 99%